2019
DOI: 10.1089/heq.2018.0082
|View full text |Cite
|
Sign up to set email alerts
|

Global Inequality in Maternal Health Care Service Utilization: Implications for Sustainable Development Goals

Abstract: Purpose: Globally, low-middle-income countries continue to account for almost all of the pregnancy-related mortalities that are largely preventable through adequate utilization of essential maternal health care services such as antenatal care (ANC) and skilled birth assistance (SBA). Promoting the use of ANC and SBA services are hindered by numerous policy- and capacity-related barriers along with widespread inequality in utilization of the existing services that further exacerbates the scenario. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 37 publications
3
80
0
Order By: Relevance
“…Using both relative and absolute inequality measures in the same study has the potential to help investigate the magnitude and trend of inequality from various dimensions and perspectives. Secondly, the study presented the inequality findings for each subgroup of the equity stratifiers, and this can assist the government to identify where and how to focus their efforts towards realization of the equity-oriented SDG in relation with maternal health [36]. Specifically, the government needs to draw increased attention to women who are poor, uneducated, live in rural areas and in most regions to increase reasonable rates of the service.…”
Section: Discussionmentioning
confidence: 99%
“…Using both relative and absolute inequality measures in the same study has the potential to help investigate the magnitude and trend of inequality from various dimensions and perspectives. Secondly, the study presented the inequality findings for each subgroup of the equity stratifiers, and this can assist the government to identify where and how to focus their efforts towards realization of the equity-oriented SDG in relation with maternal health [36]. Specifically, the government needs to draw increased attention to women who are poor, uneducated, live in rural areas and in most regions to increase reasonable rates of the service.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions designed with the assumption that economic growth translates to improved child well-being also run a high risk of being ineffective. Achieving the sustainable development goals depends on getting governments to address the gap between the rich and the poor, which is still at its highest level in decades 76…”
Section: Discussionmentioning
confidence: 99%
“…The techniques were equity gap, equity ratio, concentration curve, and concentration index. [13][14][15][16] Equity gap was used to show absolute percentage point difference in service coverage between the highest wealth quintile and the lowest, between the highest educational levels achieved and the lowest, and between urban and rural residents. The equity ratio was calculated by dividing service coverage in the top wealth quintile by that in the bottom, and service coverage among urban by that of rural dwellers.…”
Section: Discussionmentioning
confidence: 99%
“…19 Our study findings were also comparable with the findings reported in Bangladesh and other similar settings which showed the key reproductive and maternal health services were concentrated among wealthier, more educated, and women from urban areas. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][33][34][35][36] There is inter-regional disparity in the uptake of maternal health services worldwide, with the highest disparity being in Africa and Asia regions. This has huge implications in progress towards attaining SDG targets related to maternal health.…”
Section: Discussionmentioning
confidence: 99%